PERSPEKTYWY OCHRONY ŚWIATOWEGO DZIEDZICTWA W POLSCE – CZYLI TENTATIVE LIST I PROPOZYCJE MOŻLIWYCH DO ZGŁOSZENIA KANDYDATUR NA LISTĘ ŚWIATOWEGO DZIEDZICTWA - Jakub Lewicki (Ochrona Dziedzictwa Kulturowego, 2017)
The article discusses Polish suggestions of new inscriptions into the UNESCO World Heritage List. The waiting items mentioned in the Tentative List were presented. Currently the Polish version of the List numbers 5 items. They are: Gdańsk, Town of Memory and Freedom (2005), The Augustów Canal (2006), The Dunajec River Gorge in the Pieniny Mountains (2006), Extension to the Joint World Heritage Property “Primeval Beech Forests of the Carpathians (Slovak Republic and Ukraine) and the Ancient Beech Forests of Germany (Germany)” (2015), “Krzemionki”, prehistoric flint mines (2016). Other offered suggestions were also presented: The Jewish Cemetery in Łodz, the Ponds in Milicz – medieval fishponds in central Europe, Nowa Huta, the paper mill – Duszniki Zdrój, the Elbląg Canal, Nikiszowiec as a factory-related housing complex, the cultural landscape of Żuławy area, wooden mosques in the Podlasie Region – Bohoniki and Kruszyniany, the Valley of Palaces and Gardens – the Jeleniogórska Valley, Żyrardów, Warsaw Water Filters and Księży Młyn in Łodz as industrial heritage, the Citadel in Warsaw, and the Słowiński National Park as natural heritage. Among new suggestions the following were indicated: the collegiate church in Pułtusk as an example of Renaissance solutions of linear perspective applied in architecture, the project of a Gothic vault in the church in Szydłowiec as a unique example of the Gothic construction workmanship, and modern wooden churches (e.g. the church in Boguszyce).